2003
DOI: 10.1002/pros.10347
|View full text |Cite
|
Sign up to set email alerts
|

Clinical understaging in patients with prostate adenocarcinoma submitted to radical prostatectomy: Predictive value of serum chromogranin A

Abstract: PURPOSETo evaluate whether the pretreatment determination of serum chromogranin A (CgA) can provide information beyond that obtained with serum prostate specific antigen (PSA) and Gleason score at biopsy as a predictive factor of clinical understaging (T2‐pT3) of prostate adenocarcinoma.MATERIALSIn this prospective study, we analyzed 83 consecutive patients with clinical T2N0M0 prostate adenocarcinoma submitted to radical prostatectomy (RRP). On the same day of RRP, before surgery, a blood sample for the deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 20 publications
2
37
1
3
Order By: Relevance
“…Contrary to what has been reported by others (7,18,23), we were unable to find a significant correlation of preoperative serum CgA and its immunohistochemical expression with serum PSA, thereby suggesting a different behavior of neuroendocrine cells with respect to the (24,25), serum NSE in our series did not seem to be a useful tumor marker of NED in organ-confined CaP. Our data are in line with those reported by Slodkowska et al, who stated that NSE expression in the tumor and a mild increase in serum NSE are poor markers for distinguishing NED in non-small cell lung carcinomas (26).…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Contrary to what has been reported by others (7,18,23), we were unable to find a significant correlation of preoperative serum CgA and its immunohistochemical expression with serum PSA, thereby suggesting a different behavior of neuroendocrine cells with respect to the (24,25), serum NSE in our series did not seem to be a useful tumor marker of NED in organ-confined CaP. Our data are in line with those reported by Slodkowska et al, who stated that NSE expression in the tumor and a mild increase in serum NSE are poor markers for distinguishing NED in non-small cell lung carcinomas (26).…”
Section: Discussioncontrasting
confidence: 80%
“…This finding may have implications for prognosis and therapeutic strategy because of its negative influence on patient outcome. In accordance with the demonstration that serum CgA is associated with the pathological stage of the disease and that it may provide useful information on the possible clinical stage (23), circulating CgA may be used as a prognostic factor for extracapsular involvement in association with the commonly recognized pre-treatment factors for disease extent (serum PSA, clinical tumor stage and Gleason score at biopsy). In addition to Sciarra's results (23), we found that preoperative serum CgA and its immunohistochemical expression appear to be both associated with the Gleason score, which confirms that neuroendocrine features predict a poor prognosis in patients with newly diagnosed, apparently localized CaP, correlating with histological tumor undifferentiation.…”
Section: Discussionmentioning
confidence: 70%
“…The correlation with pathological stage, especially late-stage disease, has been more consistently demonstrated. 9,16 CgA may predict response to chemotherapy, 17,18 and as a marker of NE differentiation CgA has been shown to reflect androgen-independent disease even before evidence of PSA progression. 19,20 Some have suggested that CgA velocity may be useful in predicting time to androgen independence after hormonal therapy and have indicated that treatments variably accelerate NE differentiation (intermittent androgen deprivation oantiandrogen only ocastration only ocombined androgen blockade).…”
Section: Markers Of Neuroendocrine Differentiationmentioning
confidence: 99%
“…19,20 Some have suggested that CgA velocity may be useful in predicting time to androgen independence after hormonal therapy and have indicated that treatments variably accelerate NE differentiation (intermittent androgen deprivation oantiandrogen only ocastration only ocombined androgen blockade). 16,19 In the androgen-independent CaP patient, increased CgA levels appear to correlate with adverse outcomes and decreased overall survival, though levels indicative of a survival disadvantage are undefined (Table 2). 21,22 High serum levels of NSE have also been associated with adverse prognosis in metastatic CaP patients during androgen-suppression therapy, 23 but its predictive capability may be inferior to that of CgA.…”
Section: Markers Of Neuroendocrine Differentiationmentioning
confidence: 99%
“…[39] Tumors with NE features have displayed more aggression and are more resistant to hormone therapy. [25] Some studies have claimed that CgA is an independent prognostic marker for PCa, [40] while others have conflicted with these findings. [29,41] No PCa predictive values were seen for IGF-1, IGFBP-3 or CgA; AUC were 0.58, 0.55 and 0.56, respectively.…”
Section: Discussionmentioning
confidence: 99%